MODERN VIEWS ON THE PROBLEM OF GESTATIONAL DIABETES MELLITUS - Karimova Gulrukh Komilovna (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2024)
Object: Selection of an effective method of delivery for mother and child in pregnant women with gestational diabetes. Purpose of the study: Selecting the optimal method of delivery by studying the outcome of labor for the mother and fetus in women with gestational diabetes. Material and methods: The retrospective group included 67 women who passed through the regional perinatal center, city maternity complex and family clinics No. 5, No. 6 of the city of Bukhara in the periods from 2016 to 2018. The main (prospect) group consisted of 68 women whose pregnancy proceeded against the background of overt or gestational diabetes mellitus (GDM). The control group consisted of 31 women whose pregnancy proceeded physiologically.